Dedicated funding for leasing and sharing research and test facilities and its impact on innovation, follow-on financing and growth of biotech start-ups: the Mibiton case. Issue 1 (2nd January 2017) - Hulsink, Willem; Scholten, Victor
Abstract: There is a wide gap between the need for science-based start-ups to purchase or gain access to test equipment and the willingness of investors to provide the necessary funding for that. Most science-based start-ups, and in particular young biotech firms, do not have the resources needed to buy or lease the expensive facilities they need to validate their research results. Investors are reluctant to provide additional capital to these high-tech start-ups in order to acquire state-of-the-art testing equipment. Without owning or having access to the research equipment, these start-ups cannot demonstrate their scientific results effectively and are unable to seize the claims and opportunities flowing from their disclosures. Because they often lack collateral, a track record, stable cash flow and/or operational profits, science-based start-ups have to find alternative sources and channels of finance. A new government-backed funding scheme to hire and purchase and/or share research equipment, called Mibiton, was developed for the Dutch biotechnology sector to address this problem. We examine the motivation to join and participate in the Mibiton scheme, look into its (dis)advantages and evaluate its additionalities through an exploratory study among its investees. The main findings are that an active investment fund providing relatively small investments, with competitive interest rates, makes start-ups more proactive, allowing them to accelerate product development and market testing in their time-to-market race. Mibiton's investments make the start-up firms more professional, better prepared financially and, with their claims tested and validated, more future-proof. The affiliation with the Mibiton scheme also sends out a strong quality signal to the venture capital community, hereby increasing the likelihood that the start-ups will succeed in obtaining additional funding in the future.